A Review of the Phytochemical Composition and Antihypertensive Efficacy of Garlic (Allium sativum), Hibiscus (Hibiscus sabdariffa), and Ginger (Zingiber officinale) - Animashaun, Rufus Olusegun; Ajiboye, Oluwapelumi Michael; Adewumi, Aderiike; Ogunwenmo, Kayode Olusola; Animashaun, Bolanle Elizabeth (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2024)
Garlic (Allium sativum) and Hibiscus (Hibiscus sabdariffa) have been well known in conventional medicine and hold great promise not only to treat but to prevent the development of hypertension, while Ginger (Zingiber officinale) is gaining more attention in herbal circles. In this review, we present the phytochemical composition, antihypertensive effectiveness, and the mechanisms of actions of these natural remedies, with the implications in the clinical setting, also explored. Garlic is abundant in organosulfur compounds, with allicin being the most notable. These have been shown to contribute to vasodilatory effects and are associated with a numerical reduction in blood pressure. Hibiscus calyces carry in themselves anthocyanins and protocatechuic acid, which are associated with antioxidant activities and vasorelaxation properties that could act as a blood pressure regulator. The action mechanism of gingerols and shogaols, active components in ginger, suggests their possible role in strengthening blood circulation and causing the antihypertensive effect. A detailed reading of the currently available literature strongly indicates the potency of these herbs in fighting hypertension. Random clinical trials (RCTs) have demonstrated that garlic intake can bring about a modest - yet not great - reduction in blood pressure, whereas hibiscus extracts have shown diuretic, and Angiotensin-converting Enzyme (ACE) -inhibitory effects, both in animal and human experiments. Furthermore, ginger supplementation has improved blood pressure parameters, although the consensus is not as solid as those mentioned above. However, despite increased scientific evidence concerning their efficacy on health, some hurdles still exist. These challenges consist of variability in phytochemical composition, dosage standardization, poor knowledge of mechanisms, drug interactions, and safety considerations that need to be addressed through further scientific investigation. Garlic (Allium sativum), ginger (Zingiber officinale), and hibiscus (Hibiscus sabdariffa) have been used since ancient times to treat hypertension. Continued research efforts are needed to overcome these challenges to provide comprehensive therapeutic potentials and ensure safe uses in clinics for garlic, hibiscus and ginger as natural interventions for hypertension management